Hubungan Antara Risiko Pekerjaan Manual Handling Dengan Risiko Keluhan Nyeri Pinggang Pada Pekerja Kuli Panggul Di Pasar Gede Surakarta - Febri Wibowo, Indra, Tarwaka, PGDip Sc, M.Erg, Dr. Suwadji, M.Kes (2015)
Low back pain is a complaint of pain, muscle tension, or stiffness in the waist area that usually appears from manual handling job activities. Porter workers are identic with the main activity removing the object, where this kind of job is dominated by lifting, lowering, carrying, and pushing activity. This research aimed to find out the correlation risk of manual handling and risk of low back pain on porter workers at Pasar Gede of Surakarta. The research method used observational design with cross sectional approach. The subjects of this research were 36 porter workers used total sampling. The measurement of manual handling risk and low back pain risk used questionnaires. Statistical test used Kendall-Tau(t) with significance level (p<0.05). The correlation of manual handling risk and low back pain risk was acquired p=0.00 and the correlation coefficient is (r) 0.796 (strength). It is concluded that there was significant correlation between the risk of manual handling with riskof low back pain. It is better for porter workers to use tool when they are working and maintaining their physical health in doing their job.